(untitled) (Biological Sciences - PJSIR, 1999)
Effect of various blanching processes on the retention of different nutrients in carrot juice products was investigated. Maximumbrixvalueofthejuice was9.3whencarrotswereblanchedin0.05Naceticacidsolutioncontaining0.2%CaCI2 • However, brix values of thejuice obtained from unblanched and water blanched carrots were 8.1 and 8.5 respectively. Highest amount of carotene andvitamin Cwasalsofound inthejuice which wasobtained fromcarrots after blanching in aceticacidand0.2%CaCI2 solution.Otherblanchingprocessesshowedadverseeffectsontheretentionofcaroteneincarrot juice products compared with unblanched carrotjuice.